PENDIDIKAN KARAKTER ADALAH SEBUAH KEHARUSAN - Abdul Halim Rofi'ie (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2019)
Indonesia current character education is still considered as an ineffective system for building a nation’s character. The developed nations compete and prepare for facing globalization that made cultures and civilization all over the world become closer. Therefore Indonesia has to strengthen its nation resilience by focusing on character education which is, of course, not ignoring another aspect of education.The character education, in modern context, is something important to overcome Indonesian moral crisis. The moral crisis is marked by the increase number offr ee sex, cor- ruption, human rape, and homicides, including pornography and drug abuse, which until now is still cannot be completely resolved by official holders ofpolicies in this country. Therefore, It is expected that all ele- ments ofsociety  participate to improve the moral character of the nation. An inderpendent nation should construct a well-established strategy to embed code to all components of it. A good character is a pearl for a country that can be derived from the older generation to the younger, of the rulers and leaders to the people, from the teachers to the students. If the figures of a country cannot be a role modelfor  the people, so expecta- tion of improvement towards the cravig character wouldjust  be an empty hope, and it will not change anything in the country. As an effort to improve the character, the character of the nation’s children is a concern.